Comparative evaluation of two biomass direct-fired power plants with carbon capture and sequestration. (March 2020) - Yan, Linbo; Wang, Ziqi; Cao, Yang; He, Boshu
Abstract: The biomass direct-fired power plant with carbon capture and sequestration is promising to remove CO2 from air whilst generate electricity. However, the efficiencies of such power plants are usually low, and the life cycle CO2 emission of such power plants is seldom determined. To solve these issues, a novel chemical looping oxy-fired power plant with carbon capture and sequestration is proposed in this work. The proposed system is then modeled and compared with the conventional biomass air-fired plant in terms of thermodynamics and economics. All the sub-unit models of the two power plants are validated by reported data in literature. Sensitivity analyses are then implemented to investigate the effects of different key operation parameters on the system essential performance indicators. Under the optimum conditions, the power generation efficiency, the levelized cost of electricity, the CO2 capture rate, the annual power generation and the annual CO2 mitigation of the proposed system (or the conventional system) are 35.7% (31.5%), 0.0522$/kWh (0.0601$/kWh), 100% (98%), 1443.7 × 10 9  kWh/year (1241.81 × 10 9  kWh/year) and 1.191 × 10 9  t/year (1.159 × 10 9  t/year), respectively. The key findings of this work are of reference value for the construction, operation and optimization of the biomass direct-fired power plants with carbon capture and sequestration. Highlights: A CLOF-CCS power plant is proposed, modeled and compared with BAFP-CCS. The efficiency and the cost of electricity of CLOF-CCS are 35.7% and 0.0522$/kWh. The efficiency and the cost of electricity of BAFP-CCS are 31.5% and 0.0601$/kWh. The CLOF-CCS annual power yield and CO2 removal are 1443.7 × 10 9  kWh and 1.191 × 10 9  t. The BAFP-CCS annual power yield and CO2 removal are 1241.8 × 10 9  kWh and 1.159 × 10 9  t.